The Problems of and Solutions to Chinese Education for Marketing Communication at Binus University - Theresia Theresia (Humaniora, 2013)
Nowadays in Indonesia, more people realize the importance of using Chinese language. Therefore, at Binus University, Mandarin is taught not only in Chinese Literature Department, but also in non-Chinese Literature Department. Because the curriculum is still relatively new, students who have never studied Chinese language find some difficulties. The author through observations in the classroom found some problems that arise during the teaching and learning session. Through this paper, the author hopes to help to solve existing problems, to increase the level of Chinese language knowledge, and help to increase students’ interest in Chinese language.